Design Of Web-Based Information System On Monitoring The Water Quality Of Catfish Pond - Dwi Nugraheni K. (JAICT, 2017)
Water environmental factors that greatly affect the survival and growth of catfish include temperature and water pH with pH range of 6.5-8 and temperature of 250C-300C. The monitoring and measurement are still done manually by catfish farmers to get the temperature and pH parameter values without knowing the exact value of these measurements. According to those problems, this final project provides an information system on monitoring the water quality of catfish pond to facilitate monitoring, namely by using a device that is remotely controlled in real-time, and contains sensors needed for measurement so that it can measure the parameters from a different place. Each node in each pond contains a measurement system using a DS18B20 temperature sensor and a SEN0161 pH sensor that can measure temperature and pH. The system is using a method with several stages, namely the stages of design, implementation and testing. The measurement results from the temperature sensor and pH sensor are displayed on the web page in the form of graphs and tables.